Application of Quality Control using Six Sigma and Taguchi Method on UMKM Kerupuk Tahu Bangil in Pandemic Period (Case Study: UD. Sanusi) - Rizandy Bima Erlangga; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2022)
Micro, Small and Medium Enterprises (UMKM) Tofu Crackers UD Sanusi is one of the companies engaged in the MSME sector. The products produced are tofu crackers which are marketed and productive economic efforts carried out by one of the people in the Bangil area whose place is on Jl. Gen. Sudirman. diet. Pogar. district. Bangil. Pasuruan. East Java 67153. Activities of Micro, Small and Medium Enterprises (UMKM) Tofu Crackers UD Sanusi is one way for creative products to be known among the public. With the obstacles experienced by UD Sanusi's MSMEs during the pandemic, namely there were problems regarding the quality of defective products from tofu crackers during production, namely tofu crackers that were charred, tough, easily crushed, and the size of the crackers was different. Limited human resources are also one of the serious obstacles for SMEs, which are needed to maintain or improve product quality, increase efficiency and productivity in production.With these challenges, it is necessary to make systematic efforts through quality improvement, using the method used in research for quality improvement, namely six sigma, to determine the factors that affect product defects and the Taguchi method to improve the quality of the product.From the results obtained in the analysis of the hypothesis, it is known that the combination of factors that have a significant effect on the average and quality variance of tofu crackers is the same, namely flour at level 1 of 95 kg, flavoring at level 1 of 85 kg, kneading at level 1 of about 15 minutes, and drying at level 3 about 4 hours. Thus, the optimal combination of factors proved to be able to increase the average and quality variability of tofu crackers.